About the Heat Transfer Coefficient - Gareyev, А. А. (European Journal of Applied Sciences, 2024)
As an oil field is exploited, productive strata are depleted. This phenomenon is typical for many oil and gas fields. The exploitation of depleted deposits leads to complications during the operation of electric centrifugal pumps. The purpose of this work is to investigate the causes of failures and develop technological solutions.